If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + -1x)(1 + 5x) = 0 Multiply (3 + -1x) * (1 + 5x) (3(1 + 5x) + -1x * (1 + 5x)) = 0 ((1 * 3 + 5x * 3) + -1x * (1 + 5x)) = 0 ((3 + 15x) + -1x * (1 + 5x)) = 0 (3 + 15x + (1 * -1x + 5x * -1x)) = 0 (3 + 15x + (-1x + -5x2)) = 0 Combine like terms: 15x + -1x = 14x (3 + 14x + -5x2) = 0 Solving 3 + 14x + -5x2 = 0 Solving for variable 'x'. Factor a trinomial. (3 + -1x)(1 + 5x) = 0Subproblem 1
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Subproblem 2
Set the factor '(1 + 5x)' equal to zero and attempt to solve: Simplifying 1 + 5x = 0 Solving 1 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 5x = 0 + -1 5x = 0 + -1 Combine like terms: 0 + -1 = -1 5x = -1 Divide each side by '5'. x = -0.2 Simplifying x = -0.2Solution
x = {3, -0.2}
| -6y-10=32 | | 11p-14=8 | | 9/5-1=4 | | 8x-4=2x+4 | | 10z+11=101 | | 11y+3=47 | | 2(4x+4)=3(2x+1) | | 5f-5=8f-20 | | 8z+5=53 | | 15x-3=13x-5 | | 8y-3=85 | | 8z-6=34 | | 10z+8=78 | | 144/x=4/9x | | 4x+40=9x+5 | | 1.5-0.05x=3 | | tanx=5/2 | | 4x-2x+1.75=4 | | 12x-28x+15=0 | | (x+5)4=56 | | 8z+10=34 | | 5y+6x=-7 | | 6z+10=28 | | 3x-2b=8 | | Sin12=36/x | | 3x+4=-5y | | (u+1)10=50 | | (1-4)-4=-4x-(4-3x) | | 1.5-0.005x=3 | | 10/x^2-1/y=1/5 | | (q-8)5=45 | | 5v+16=-9 |